SINKRONISASI E-LOGBOOK SEBAGAI INTEGRASI AKTIVITAS KLINIS KEPERAWATAN DALAM IMPLEMENTASI JENJANG KARIR PROFESSIONAL PERAWAT - Ida, Ida; Susilaningsih, Sri; Rohayani, Lilis; Inayah, Iin; Oyoh, Oyoh (Jurnal Manajemen Kesehatan Indonesia, 2025)
Research objective to synchronize clinical nurse competency authority items and create an E-logbook documentation design. The research method uses Research and Development (R&D). The sampling technique was based on purposeful sampling with 8 informants. The formation of a grouping list of competency authority items based on the synchronization of several policies which are used as a reference for the implementation of career paths and E-logbook documentation design. Synchronization of nurse competency authority items in logbook documentation grouped based on functional position level which is adjusted to the level of Clinical Nurse (PK) making it easier to document the E-logbook. Ther are need to be support from hospital leaders, the care sector and related stkeholder to follow up on the implementation of research result, the PPNI organization needs to follow up on a form of synchronization of effective points, and further researchers to carry out trials of the synchronization results so that they can used as a basis for synchronization with other nursing areas.